2021
DOI: 10.1055/a-1546-8727
|View full text |Cite
|
Sign up to set email alerts
|

Colon capsule endoscopy in colorectal cancer screening: Interim analyses of randomized controlled trial CareForColon2015

Abstract: Background and study aims The Danish CareForColon2015 trial, launched in 2020 as part of the Danish Colorectal Cancer Screening program, is the largest randomized controlled trial to date on colon capsule endoscopy (CCE). This paper presents the interim analysis with the objective of ensuring the safety of patients in the intervention group and evaluating the clinical performance of the trial’s predefined clinical parameters. Patients and methods We evaluated the initial 234 CCEs according to quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In particular, less than 50% of the examinations were both complete and with adequate bowel preparation; and the authors concluded that improvement would be needed to increase the reliability of CCE, since most of the missed colonic advanced neoplasia were due to incomplete CCE with distal neoplasia location [ 86 ]. In analogy to this, the previously discussed Danish trial also reported a lower-than-expected completion rate, and discussed ways to optimize that [ 50 ]. In the 2021 meta-analysis by Kjølhede et al, the rate of patients with adequate bowel preparation varied from 40% to 100%, and the rates of complete CCE transit varied from 57% to 100%.…”
Section: Limitations In the Use Of Colon Capsule Endoscopymentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, less than 50% of the examinations were both complete and with adequate bowel preparation; and the authors concluded that improvement would be needed to increase the reliability of CCE, since most of the missed colonic advanced neoplasia were due to incomplete CCE with distal neoplasia location [ 86 ]. In analogy to this, the previously discussed Danish trial also reported a lower-than-expected completion rate, and discussed ways to optimize that [ 50 ]. In the 2021 meta-analysis by Kjølhede et al, the rate of patients with adequate bowel preparation varied from 40% to 100%, and the rates of complete CCE transit varied from 57% to 100%.…”
Section: Limitations In the Use Of Colon Capsule Endoscopymentioning
confidence: 97%
“…These studies signaled the markedly improved sensitivity and accuracy of CCE-2 compared to CCE-1. Several subsequent controlled studies have reported the efficacy of CCE-2 in identifying colonic polyps [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: 2nd-generation Colon Capsule Endoscopy and Polyp Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1–6 In complete CCE investigations, polyp detection rates (PDR) for large polyps and complications appear to be equivalent or better than those reported from conventional optical colonoscopy. 1 , 7 , 8 One of the drawbacks in CCE is the high proportion of incomplete examinations 9 leading to patients needing additional investigations. Incomplete CCE investigations can be caused by inadequate bowel cleansing or a transit time exceeding the battery lifetime.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The interim analysis from this trial was published in the summer of 2021, revealing a CCE completion rate of 67.9%, which was lower than expected. 7 This elicited an examination of how to improve the completion rate by adjusting the bowel preparation regimen. 10 Adding prucalopride (Resolor ® ) to the regimen prior to capsule ingestion seemed a logical adjustment.…”
Section: Introductionmentioning
confidence: 99%